A guinea pig's tale: learning to review end-to-end marine ecosystem models for management applications - Kaplan, Isaac C.; Marshall, Kristin N. (ICES journal of marine science, 2016)
A shift towards ecosystem-based management in recent decades has led to new analytical tools such as end-to-end marine ecosystem models. End-to-end models are complex and typically simulate full ecosystems from oceanography to foodwebs and fisheries, operate on a spatial framework, and link to physical oceanographic models. Most end-to-end approaches allow multiple ways to implement human behaviours involving fishery catch, fleet movement, or other impacts such as nutrient loading or climate change effects. Though end-to-end ecosystem models were designed specifically for marine management, their novelty makes them unfamiliar to most decision makers. Before such models can be applied within the context of marine management decisions, additional levels of vetting will be required, and a dialogue with decision makers must be initiated. Here we summarize a review of an Atlantis end-to-end model, which involved a multi-day, expert review panel with local and international experts, convened to challenge models and data used in the management context. We propose nine credibility and quality control standards for end-to-end models intended to inform management, and suggest two best practice guidelines for any end-to-end modelling application. We offer our perspectives (as recent test subjects or “guinea pigs”) on how a review could be motivated and structured and on the evaluation criteria that should be used, in the most specific terms possible.